Riesz Representation Theorem on Bilinear Spaces of Truncated Laurent Series - Sabarinsyah Sabarinsyah; Hanni Garminia; Pudji Astuti (Institute for Research and Community Services (LPPM) ITB, 2017)
In this study a generalization of the Riesz representation theorem on non-degenerate bilinear spaces, particularly on spaces of truncated Laurent series, was developed. It was shown that any linear functional on a non-degenerate bilinear space is representable by a unique element of the space if and only if its kernel is closed. Moreover an explicit equivalent condition can be identiï¬ed for the closedness property of the kernel when the bilinear space is a space of truncated Laurent series.